EFEKTIVITAS PENGGUNAAN SOFTWARE MUSIK BAGI PROSES BELAJAR MENGAJAR - Sema, Daniel (Sekolah Tinggi Teologi Kristus Alfa Omega, 2017)
Computer information technology and software have been a lot of ease in teaching and learning process. Through internet searching learning materials easier to do; with powerpoint lecturers more easily explain the course material to students. In addition to being interesting, the delivery can be done more quickly and practically than by using conventional methods. For lecturers and music students of the church, music software is very helpful in the process of teaching and learning, because with this medium (up-to-date) what can not be done by someone manually will be realized quite satisfactorily, for example arranging orkestrasi or make arrangements with SATB format or with many musical instruments. The result is certainly more real and effective.